PERAN PEMERIKSA AKUNTANSI DALAM PENCEGAHAN DAN PENGUNGKAPAN KECURANGAN (FRAUD) : STUDI KASUS PADA PT. PMS3G - Ningrum, Paulina Putri; Miharja, Kasmanto; Dwiyanti, Salsabilla; Salsabilla, Malika (Universitas Trilogi, 2024)
This research uses a qualitative descriptive method to determine the role of accounting examinations in preventing and disclosing fraud, especially in the case of PT.PMS3G. This research uses secondary data from previous journals. The result showed that accounting examinations play an important role in discovering and preventing fraud. Companies with strong internal controls can lower the likelihood of fraud and increase their transparency and accountability.Keywords: Accounting examiner; Fraud; Fraud prevention; Internal audit